Manajemen Mutu Pendidikan dalam Perspektif Kebijakan Pendidikan Nasional dan Islam - Sunoto; Rosyid, M. Abdul; Yulianto (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2023)
The low quality of education in Indonesia is actually a long-standing discussion. But until now the quality of education is also finished. Quality education is the expectations and demands of all stakeholders in education. Everyone will certainly prefer menntut science at an institution that has a good quality. On this basis, schools / educational institutions should be able to provide good service and quality in order not to be abandoned and unable to compete with other educational institutions. From a variety of views, criteria and indicators that we can take that quality education could be improved if the school has one) support from the government, 2) Leadership Principals effective, 3) Performance good teacher, 4) relevant curriculum 5) graduates quality, 6) culture and climate of effective organization, 7) the support of the community and parents. Implementation of management in improving the quality of education is a real solution is to be hope in order to manage the indicators of the quality of education to create a synergy in efforts to improve the quality of education